Group III nitride nanomaterials for biosensing. Issue 22 (22nd May 2017) - Li, Xiao; Liu, Xinyu
Abstract : We present a comprehensive review on biosensor development with III–nitride nanomaterials, starting from the material properties of III–nitrides and focusing on surface treatments, biosensing mechanisms, and applications. Abstract : Biosensing has found wide applications in biological and medical research, and in clinical diagnosis, environmental monitoring and other analytical tasks. Recognized as novel and outstanding transducing materials because of their superior and unique physical/chemical properties, group III nitride (III–nitride) nanomaterials have been introduced into biosensor development with remarkable advancements achieved in the past few decades. This paper presents the first comprehensive review on biosensor development with III–nitride nanomaterials. The review starts with the introduction of the material properties and biocompatibility of III–nitrides that are useful for biosensing. The focus is then placed on surface treatments of III–nitrides, which lay the foundation for biosensing, and on biosensing mechanisms where the exceptional properties of III–nitride nanomaterials lead to superior biosensing performance. From a practical point of view, techniques for biosensor fabrication are then summarized. Finally, existing biosensing applications and future directions are discussed.